The Reform Movement of KH. Wahid Hasyim: Da’wah Management and the Transformation of Islamic Education in Indonesia - Ashari, M. Fahmi; Derysmono, Derysmono; Fikri, Muhammad Rozan (An-Nida', 2024)
KH. Wahid Hasyim was a key figure in the reform of Islamic education and da’wah management in Indonesia. This study aims to explore the reform movement of KH. Wahid Hasyim in the context of da’wah management and the transformation of Islamic education in Indonesia. This research employs a qualitative approach by analyzing various literature sources on the educational and managerial policies introduced by KH. Wahid Hasyim, as well as his contributions to the modernization of pesantren. The findings indicate that KH. Wahid Hasyim implemented modern management principles in the administration of Islamic education and da’wah. He integrated religious education with general knowledge, such as foreign languages, to equip students with the necessary skills to face contemporary challenges. The reforms carried out at Madrasah Nizamiyah, including curriculum modifications and teaching method improvements, led pesantren toward a more modern educational system that aligns with societal needs. His policies, such as mandating religious education in public schools, reflect his commitment to the advancement of Islamic education in Indonesia. KH. Wahid Hasyim’s contributions to Islamic education can also be seen in his efforts to develop educational institutions, such as LP Ma'arif NU, which now oversees more than 6,000 educational institutions across Indonesia. With an inclusive approach rooted in the values of tolerance, his educational reforms not only emphasized academic excellence but also focused on character development, preparing students to navigate global challenges.Abstrak: KH. Wahid Hasyim merupakan salah satu tokoh penting dalam pembaharuan pendidikan Islam dan manajemen dakwah di Indonesia. Tujuan penelitian ini adalah untuk menggali gerakan pembaharuan KH. Wahid Hasyim dalam konteks manajemen dakwah dan transformasi pendidikan Islam di Indonesia yang diusungnya. Penelitian ini menggunakan pendekatan kualitatif dengan menganalisis berbagai sumber kepustakaan mengenai kebijakan pendidikan dan manajerial yang diperkenalkan oleh KH. Wahid Hasyim, serta bagaimana kontribusinya dalam modernisasi pesantren. Hasil penelitian menunjukkan bahwa KH. Wahid Hasyim menerapkan prinsip-prinsip manajemen modern dalam pengelolaan pendidikan Islam dan dakwah. Wahid mengintegrasikan pendidikan agama dengan pengetahuan umum, seperti bahasa asing, untuk mempersiapkan santri menghadapi tantangan zaman. Pembaharuan yang dilakukan di Madrasah Nizamiyah, termasuk perubahan kurikulum dan metode pengajaran, membawa pesantren menuju pendidikan yang lebih modern dan relevan dengan kebutuhan masyarakat. Kebijakan-kebijakan yang diterapkan, seperti mewajibkan pendidikan agama di sekolah umum, menunjukkan komitmennya terhadap perkembangan pendidikan Islam di Indonesia. Kontribusi KH. Wahid Hasyim dalam dunia pendidikan Islam dapat dilihat melalui upayanya dalam mengembangkan lembaga pendidikan, seperti LP Ma’arif NU, yang kini memiliki lebih dari 6000 lembaga pendidikan di seluruh Indonesia. Dengan pendekatan inklusif dan berbasis pada nilai-nilai toleransi, pendidikan yang dibentuk tidak hanya berfokus pada aspek akademik, tetapi juga pada pembentukan karakter yang dapat menghadapi tantangan global.